2015
DOI: 10.1111/dech.12210
|View full text |Cite
|
Sign up to set email alerts
|

Contentious and Prefigurative Politics: Vigilante Groups’ Struggle against Sexual Violence in Egypt (2011–2013)

Abstract: This article analyses the drivers, mobilizational tactics and manoeuvrings of informal, youth-led initiatives that emerged in post-Mubarak Egypt to counter the growing threat of sexual violence against women in public spaces. The findings are based on empirical research into youth-led activism against gender-based violence during 2011-2013. The approach adopted is a case study of three initiatives, Bassma (Imprint), Shoft Taharosh (Harassment Seen) and Opantish (Operation Anti Sexual Harassment). Informal yout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Often disenchanted with mainstream multilateral forums of discussion and the performance of national governments, these movements and institutions sought prefigurative action as a way to achieve change. This included organisations such as the World Social Forum (Fominaya, 2010), the Occupy Movement (Brissette, 2013;Halvorsen, 2017), and various facets of the collection of uprisings and assertions known as 'the Arab Spring' in North Africa and the Middle East (see Tadros, 2015). Occupy is usually taken as emblematic.…”
Section: Prefigurative Politicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Often disenchanted with mainstream multilateral forums of discussion and the performance of national governments, these movements and institutions sought prefigurative action as a way to achieve change. This included organisations such as the World Social Forum (Fominaya, 2010), the Occupy Movement (Brissette, 2013;Halvorsen, 2017), and various facets of the collection of uprisings and assertions known as 'the Arab Spring' in North Africa and the Middle East (see Tadros, 2015). Occupy is usually taken as emblematic.…”
Section: Prefigurative Politicsmentioning
confidence: 99%
“…In a related manner, Barron (2017) argues that community gardening has persuaded people to think about the long-term use value of local space as well as its market worth, and Bolton et al (2016) refer to how Occupy activists challenged dominant notions of idleness and 'dirt'. A key example of the effectiveness of prefigurative politics in changing attitudes is also is situations in which women seek to bring 'private' spaces of the domestic sphere into public settings (see Silvey, 2005;Klodawsky, et al 2013) or show through bodily performances alternative ways of acting in the world (Tadros, 2015). For example, Klodawsky et.…”
Section: Impactmentioning
confidence: 99%
“…As Tadros explains, "It was found that those most active in countering gender-based violence in public spaces post-Mubarak were collective actors who happened to be informal, youth-led and engaged in street activism. Within that cohort of informal actors, through a process of corroboration of evidence and triangulation of methods, it appeared at that time that the three most influential initiatives were Shoft Taharosh (Harrassment Seen), Bassma (Imprint) and Opantish (Operation Against Sexual Harassment)" (Tadros 2015). Tadros goes on to note that the changes that these young people sought to create in how streets and public spaces were transformed to become safer also transformed their own inner presumptions of their own gendered attributes.…”
Section: Youth and Organizingmentioning
confidence: 99%
“…Tadros goes on to note that the changes that these young people sought to create in how streets and public spaces were transformed to become safer also transformed their own inner presumptions of their own gendered attributes. Expectations around hegemonic masculinities to perform savior roles of the othered feminine, assumptions that maleness is able to remove the feminine from violent spaces, and how the operations of their street activism were divided across gendered and labor lines were all challenged throughout this time (Tadros 2015). The affirmative and collective action undertaken by these young people challenged the assumptions placed upon them, that being that youth were not considered to be lazy or powerless, nor to be seen solely as victims and collateral of violence.…”
Section: Youth and Organizingmentioning
confidence: 99%
“…There has been a noticeable upsurge of prefigurative action in this sense since the mid‐1990s. This has been manifest in the rise of the World Social Forum (Fominaya, ), Occupy Movement (Schneider, ; Van De Sande, ), various facets of the collection of uprisings and assertions known as “the Arab Spring” in North Africa and the Middle East (see Tadros, ). It is also evident in a wide variety of other forms of political assertion during recent years, including the squatters’ movements (Vasudevan, 2015b), environmental activism (Mason, ), community garden initiatives (Guerlin & Campbell, ), community‐based recovery groups (Beckwith et al., ), alternative economies (White & Williams, ) and internet‐based political struggle (Sancho, ).…”
Section: Prefigurative Politicsmentioning
confidence: 99%